Helicobacter pylori in children. - Sullivan, P. B. (BMJ Group, 1991)
The clinical manifestations of Helicobacter pylori (formerly Campylobacter pylori) infection in children overlap with those encountered in adults but there are some important differences. The aim of this review is to describe the range of manifestations of this infection in children, together with means of diagnosis and treatment.